Working with custodial grandparents - Hayslip, Bert, Jr; Hicks-Patrick, Julie (Springer Pub. Co., 2003)
The 18 papers of this collection on grandparents who raise their grandchildren are grouped into the broad categories of theory, practical applications, and empirical studies. Individual topics include case studies, intervention research, support groups, cross-discipline approaches to establishing caregiving guidelines, the psychological adaptation of grandchildren, building parenting skills, and grandparent caregivers of children with developmental disabilities. The contributors teach psychology, social work, child development, and gerontology at universities in the US.